PENGARUH MODAL KERJA BERSIH DAN PENJUALAN TERHADAP LABA BERSIH PT. INDOFOOD SUKSES MAKMUR TBK PERIODE 2013-2022 - Anggraeni, Lisa; Kusmawati, Yeti (Journal of Research and Publication Innovation, 2024)
During the pandemic, the food industry in Indonesia, especially staple foods such as Indome, which were easy to consume and had relatively cheap prices, was very popular with the public. At the start of the pandemic from 2020 to 2022, net working capital and sales of PT. Indofood is increasing, while in 2022 net profit will decrease. This research aims to determine the effect of net working capital and net sales both partially and simultaneously on net profit. Net working capital and net sales are used as independent variables, while net profit is used as the dependent variable. This thesis uses research methods with a quantitative approach. The population in this study was PT. Indofood Sukses Makmur Tbk. The number of samples in this research is financial reports for 10 years of research. Statistical data analysis techniques using SPSS (Statistical Package for Social Sciences) 26.0 for Windows program tools, namely multiple linear regression analysis with t-test and F-test. The multiple linear regression analysis test carried out on the first hypothesis has a t value of (-0.467) and a significance of 0.655 indicating that partially working capital has no effect on net profit. In the second hypothesis test the t value is (5.184) and a significance of 0.001 indicating that partially sales has an effect on net profit, and in the F test for the third hypothesis the F value is (14.385) and a significance of 0.003 shows that net working capital and sales simultaneously influence net profit. The coefficient of determination (R Square) value is 0.748, this shows that the variance of the independent variable is able to explain 74.8% of the dependent variable, while the remaining 25.2% is explained by other variables not examined in this research.